A gestão participativa do processo decisório das casas familiares rurais da região sudoeste do Paraná: estudo de caso nas CFR’s de Pato Branco e Manfrinópolis - Straub, Polyane Passos Mayer (2013)
This research aimed to identify the decision making process as it occurs in the Rural Family Houses in Manfrinópolis and Pato Branco municipalities, located in southwest region of Paraná. Some surveys were carried out, among them bibliography, documentary and exploratory. The bibliography search was performed by reading books, articles, thesis and dissertations on the participative management subject; materials on the constitution of Rural Family Houses, as well as the context of the Pedagogy of Alternation, which is crucial for this study. The document research verified documents governing the operation of Rural Family Houses, in other words, the Statute of Association of each RFH, it was also researched the Regional Rural Family Houses Association Statute in Southern Brazil. The Exploratory research was through a data collecting, which occured as follows: semi-structured interview guide with the RFHs coordinators, members of the Association of RFHs. President and the Regional Rural Family Houses Association in Southern Brazil Educational Adviser and Project organizer. For the processing of the documents was verified the existence of the term and form of participative management constitution and the role of each member of the Association of CFRs. The study was conducted in three stages. The first was held at the construction stage of the research, in other words, contextualized to the southwest region of Paraná and the municipalities of Manfrinópolis and Pato Branco. The second part consists of a referential literature on participative management and also brings the historical constitution of RFHs, its appearance in France, Brazil and southern Brazil. The third part contains the results concerning to the data collection done. The results obtained in the research highlighted the financial difficulties that the RFHs face, considering that they need help from government agencies, NGOs or private companies. These financial constraints end up involving other pedagogical factors such as, for example, lack of adequate structure of the RFHs. But the survey also showed some interesting data, such as improved performance and behavior of young people in relation to traditional school previously attended by those young people. Also according to those surveyed RFH helps keep the young in the field with a Professional Life Project, considering that it is necessary to encourage them to remain in rural areas, but they are still able to increase their income.